Elevated expression of periostin in human osteoarthritic cartilage and its potential role in matrix degradation via matrix metalloproteinase‐13. Issue 10 (19th June 2015) - Attur, Mukundan; Yang, Qing; Shimada, Kohei; Tachida, Yuki; Nagase, Hiroyuki; Mignatti, Paolo; Statman, Lauren; Palmer, Glyn; Kirsch, Thorsten; Beier, Frank; Abramson, Steven B.
ABSTRACT: We investigated the role of periostin, an extracellular matrix protein, in the pathophysiology of osteoarthritis (OA). In OA, dysregulated gene expression and phenotypic changes in articular chondrocytes culminate in progressive loss of cartilage from the joint surface. The molecular mechanisms underlying this process are poorly understood. We examined periostin expression by immunohistochemical analysis of lesional and nonlesional cartilage from human and rodent OA knee cartilage. In addition, we used small interfering (si) RNA and adenovirus transduction of chondrocytes to knock down and up‐regulate periostin levels, respectively, and analyzed its effect on matrix metalloproteinase (MMP)‐13, a disintegrin and MMP with thrombospondin motifs (ADAMTS)‐4, and type II collagen expression. We found high periostin levels in human and rodent OA cartilage. Periostin increased MMP‐13 expression dose [1‐10 μg/ml (EC50 0.5‐1 μg/ml)] and time (24‐72 h) dependently, significantly enhanced expression of ADAMTS4 mRNA, and promoted cartilage degeneration through collagen and proteoglycan degradation. Periostin induction of MMP‐13 expression was inhibited by CCT031374 hydrobromide, an inhibitor of the canonical Wnt/β‐catenin signaling pathway. In addition, siRNA‐mediated knockdown of endogenous periostin blocked constitutive MMP‐13 expression. These findings implicate periostin as a catabolic protein that promotes cartilage degeneration in OA by up‐regulating MMP‐13 through canonical Wnt signaling.—Attur, M., Yang, Q., Shimada, K., Tachida, Y., Nagase, H., Mignatti, P., Statman, L., Palmer, G., Kirsch, T., Beier, F., Abramson, A. B. Elevated expression of periostin in human osteoarthritic cartilage and its potential role in matrix degradation via matrix metalloproteinase‐13. FASEB J. 29, 4107‐4121 (2015). www.fasebj.org